A new species of Dicranophora Macquart (Diptera, Stratiomyidae) from Bahia State, Brazil and a key to species of the genus - Godoi, Fabio Siqueira Pitaluga de; Rafael, José Albertino (Zootaxa, 2013)
A new species of the Neotropical Dicranophora Macquart is described and illustrated from six males collected in northeast Brazil, Bahia state (Encruzilhada district). Dicranophora femurspiculata sp. nov. is characterized by the specific pattern of spots on the frons, on the legs and on the abdomen, and by a distinct shape of the scutellar process and mid femur. A key to the species of the genus and a distribution map are presented. Copyright © 2013 Magnolia Press.
Keywords: Brachycera; Dicranophora; Diptera; Raphiocerinae; Stratiomyidae; Anatomy And Histology; Animals; Animals Structures; Body Size; Classification; Diptera; Female; Growth, Development And Aging; Male; Organ Size; Animals Structures; Animal; Body Size; Diptera; Female; Male; Organ Size